Retroperitoneal lymphangioma in a pregnant patient: A case report and literature review - Isabela Sánchez Mayorca; Mónica Viviana Ramírez Cifuentes; Diana Marcela Hoyos Guerrero; Roberto Gallo Roa; Santiago Vieira Serna; Rafael Leonardo Aragón Mendoza (Elsevier, 2024)
This case report describes the management of a woman diagnosed with a retroperitoneal cystic tumor during pregnancy. The 29-year-old patient presented at 29 weeks of pregnancy with abdominal pain. A retroperitoneal tumor measuring 224 × 156 × 235 mm was identified on ultrasound and magnetic resonance imaging. The patient underwent cesarean section delivery of a healthy neonate at 37 weeks. Uncomplicated laparoscopic surgery was performed during the postpartum period, resulting in a histologic diagnosis of a retroperitoneal lymphangioma. A review of articles published between 2003 and 2023 on the diagnosis, management, and prognosis of gestational lymphangiomas was conducted using the PubMed, SCOPUS and SpringerLink databases. Ten articles, including case reports of lymphangiomas diagnosed during pregnancy, were identified. The most frequent location was the gastrointestinal tract, with no cases reported in the retroperitoneal area. A good perinatal outcome was reported in the majority of cases. Lymphangiomas are rare benign tumors that are even more uncommon during pregnancy. Watchful waiting can offer a good obstetric and perinatal prognosis.